The Impact of Child-Centered Teaching Approaches and Teacher Interaction on Learning Engagement among Early Childhood Students in Indonesia - Riki Taufiki; Lamri Siti Hasanah Nadeak; Istiarsyah Istiarsyah (Eastasouth Institute, 2026)
Student learning engagement is a key factor in determining the effectiveness of early childhood education, as active participation and enthusiasm influence children's cognitive and social development. This study examines the impact of child-centered teaching approaches and teacher interaction on student learning engagement in early childhood education in Indonesia. Using a quantitative survey method, data were collected from 200 early childhood education teachers through a Likert-scale questionnaire and analyzed using SPSS version 25, including descriptive statistics, validity and reliability tests, and multiple linear regression analysis. The results show that both child-centered teaching approaches and teacher interaction have a positive and significant effect on student learning engagement, with teacher interaction showing a stronger influence. The two variables jointly explain 50.7% of the variance in student learning engagement. These findings emphasize the importance of interactive, child-centered learning environments and strong teacher–student communication to enhance student engagement in early childhood education.